Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages atives in the factory. It should be noted that women and juveniles cannot be compelled to work hours in excess of those laid down in the Factories Act. At the end of 1940, there were 5,493 factories holding permissions for one or other of the following schemes: A. Three shifts. Women and Male Young Persons 16—18. 1. No shift to exceed 8 hours. 2. Period: Morning shift not to start before 6 a.m. Afternoon shift not to end after 11 p.m. 3. Not more than 7 turns in 8 days; but individual shall have one day (24 hours) off in every 7 or 8 days. 4. Fixed interval of at least half-hour during each spell. 5. Messroom with seats with backrests, tables, means of heating food and boiling water. 6. Supervisor (one of themselves will do) for women on night shift. B. Two Day Shifts. Women and Young Persons of both sexes, 16—18. 1. Each shift 8 hours. 2. } 3. } 4. } as above. 5. } C. Day and Night Shift. Women and Male Young Persons 16—18. 1. Total hours of each shift not more than 60 per week. 2. Not more than 7 turns in 8 days; but individual should have twenty-four hours off in seven days. 3. Night turn not to be worked by women or young persons for more than two weeks, or at most four weeks consecutively. (If they want to, they can go on permanent night shift.) 4. Spell of work can be extended to six hours if quarter-hour rest given: refreshment must be made ready for workers the moment they stop. 5. Messroom (as above) to be provided. 6. Night supervisor for Women (may be one of themselves). D. Extended Day Work. (i) Women and Young Persons 16—18 (both sexes). 1. Not more than 60 hours per week. 2. Not more than 11 hours' work on five days, and not more than nine hours on the sixth day (Period of employment, 13 hours and 10 hours.) 6 a.m.— 9 p.m. (ii) Young Persons under 16. 1. Not more than forty-eight hours per week; not more than nine hours per day and five hours on the sixth day. Period of employment, 11 hours and 5 hours between 6 a.m.— 6 p.m. (i) and (ii) One free day off per week for all. Of the 5,493 factories operating these, in only 171 was a system of three shifts asked for, and in only 282 a system of two shifts. Some managements may still be working hours in excess of these 26 21/2049